Epidemiology of CVD Risk Factors and Gender Differences - Nur Aifiah Binti Ibrahim; Muhammad Ali Haider (INHEALTH : INDONESIAN HEALTH JOURNAL, 2024)
Background: Cardiovascular diseases (CVDs) can either be symptomatic or asymptomatic for many people. Until now, they are still unaware of their manifestations. Thus, risk factors can help to strategise in managing and controlling the signs and symptoms of CVDs. Men are more prone to the adversity of health outcomes, including CVD. However, women tend to have a worse condition if the symptoms prevail. Therefore, taking into account the gender-related differences in the incidences of CVD might help in risk management and profiling the specific attributes that may contribute to the development of CVD itself. The Aim of Study: To enlist and give an overview of the gender differences in pursuing CVD health equality and prevent them from developing CVD. Method: A narrative review based on general statements and simple knowledge to give them the overall picture of CVD among men and women. Results: Overall, the CVD classifications for men and women can be differentiated by their hormonal changes, daily nutrient intakes, physical exercises, and treatment strategies. Conclusion: In conclusion, early detection may prevent the progression of CVD and minimise the risk of developing it.